Potential of palm oil clinker as reinforcement in aluminium matrix composites for tribological applications - Y. B., Zamri; Shamsul Baharin, Jamaludin, Prof. Dr.; Mohammed Misbahul, Amin, Prof. Madya Dr. (University of Malaya, 2011)
Link to publisher's homepage at http://www.um.edu.my/